The Role of the 2024 Summit of the Future towards the 2030 Sustainable Development Goals in Indonesia's Economic Sector in Papua - Adhimah, Thalabat Arrahmatal; Redjosari, Slamet Muliono (Politeia : Journal of Public Administration and Political Science and International Relations, 2024)
This journal discusses the role of the 2024 Summit of the Future towards the 2030 Sustainable Development Goals Program in Indonesia and why Indonesia is so active in contributing to this agenda. Indonesia's achievements in sustainable development reaching the world average become interesting to understand Indonesia's need to join the Summit of the Future 2024. This method employs a qualitative and descriptive approach. In data collection, the author uses secondary data from the study literature. The concepts of sustainable development and multilateral cooperation are very helpful in analyzing the issues raised. The results of the author's research found that Indonesia's interest in actively joining the Summit of the Future 2024 was due to the challenges faced by Indonesia in carrying out sustainable development to demonstrate Indonesia's commitment to contribute to the 2030 Sustainable Development Goals Programme agenda. Indonesia's participation in the Summit of the Future 2024 is expected to open up further opportunities for Indonesia to carry out multilateral cooperation to meet Indonesia's needs in carrying out sustainable development.